Biological impact of preschool music classes on processing speech in noise - Strait, Dana L. (Elsevier, 2013)
Musicians have increased resilience to the effects of noise on speech perception and its neural underpinnings. We do not know, however, how early in life these enhancements arise. We compared auditory brainstem responses to speech in noise in 32 preschool children, half of whom were engaged in music training. Thirteen children returned for testing one year later, permitting the first longitudinal assessment of subcortical auditory function with music training. Results indicate emerging neural enhancements in musically trained preschoolers for processing speech in noise. Longitudinal outcomes reveal that children enrolled in music classes experience further increased neural resilience to background noise following one year of continued training compared to nonmusician peers. Together, these data reveal enhanced development of neural mechanisms undergirding speech-in-noise perception in preschoolers undergoing music training and may indicate a biological impact of music training on auditory function during early childhood.